2015
DOI: 10.1038/ismej.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Habitat-specific environmental conditions primarily control the microbiomes of the coral Seriatopora hystrix

Abstract: Reef-building corals form complex relationships with a range of microorganisms including bacteria, archaea, fungi and the unicellular microalgae of the genus Symbiodinium, which together form the coral holobiont. These symbionts are known to have both beneficial and deleterious effects on their coral host, but little is known about what the governing factors of these relationships are, or the interactions that exist between the different members of the holobiont and their environment. Here we used 16S ribosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
124
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(137 citation statements)
references
References 116 publications
13
124
0
Order By: Relevance
“…Endozoicomonas are Gammaproteobacteria frequently observed in reef‐building corals (Bayer et al., 2013; Bourne et al., 2008; Glasl, Herndl, & Frade, 2016; Neave, Michell, et al., 2017; Neave, Rachmawati, et al., 2017; Pantos, Bongaerts, Dennis, Tyson, & Hoegh‐Guldberg, 2015; Pogoreutz, Rädecker, Cárdenas, Gärdes, Wild, et al., 2017) and highly dominant in pocilloporid hosts where they were found to reside deep within the gastrovascular tissues (Bayer et al., 2013; Neave, Rachmawati, et al., 2017). More generally, Endozoicomonas are commonly assumed to provide an important role in coral holobiont functioning due to their widespread prevalence and high abundance in many coral species (Bayer et al., 2013; Gignoux‐Wolfsohn, Aronson, & Vollmer, 2017; Glasl et al., 2016; Jessen et al., 2013; Meyer, Gunasekera, Scott, Paul, & Teplitski, 2016; Neave et al., 2016; Neave, Rachmawati, et al., 2017) and apparent metabolic versatility (Ding, Shiu, Chen, Chiang, & Tang, 2016; Hyun et al., 2014; Neave, Michell, et al., 2017; Yang et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Endozoicomonas are Gammaproteobacteria frequently observed in reef‐building corals (Bayer et al., 2013; Bourne et al., 2008; Glasl, Herndl, & Frade, 2016; Neave, Michell, et al., 2017; Neave, Rachmawati, et al., 2017; Pantos, Bongaerts, Dennis, Tyson, & Hoegh‐Guldberg, 2015; Pogoreutz, Rädecker, Cárdenas, Gärdes, Wild, et al., 2017) and highly dominant in pocilloporid hosts where they were found to reside deep within the gastrovascular tissues (Bayer et al., 2013; Neave, Rachmawati, et al., 2017). More generally, Endozoicomonas are commonly assumed to provide an important role in coral holobiont functioning due to their widespread prevalence and high abundance in many coral species (Bayer et al., 2013; Gignoux‐Wolfsohn, Aronson, & Vollmer, 2017; Glasl et al., 2016; Jessen et al., 2013; Meyer, Gunasekera, Scott, Paul, & Teplitski, 2016; Neave et al., 2016; Neave, Rachmawati, et al., 2017) and apparent metabolic versatility (Ding, Shiu, Chen, Chiang, & Tang, 2016; Hyun et al., 2014; Neave, Michell, et al., 2017; Yang et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Coral microbiomes are shown to vary to a degree across spatial, depth, and environmental distributions (Pantos et al, 2015;Roder et al, 2015;Hernandez-Agreda et al, 2016;Glasl et al, 2017). Rapid adjustment of the microbiome has also recently been reported under stressful environmental conditions and suggested to support holobiont functioning (Röthig et al, 2016;Ziegler et al, 2017).…”
Section: Microbiome Flexibility Aligns With Phenotypic Plasticitymentioning
confidence: 99%
“…studies (e.g., Littman et al, 2009;Pantos et al, 2015;Roder et al, 2015) have suggested that geographic location and environmental settings can determine the holobiont microbiome, whereas others (e.g., Hentschel et al, 2002;Fraune and Bosch, 2007;Montalvo and Hill, 2011;Lawler et al, 2016) have shown that bacterial communities are species-specific associations conserved over time and space. Moreover, coevolution of bacteria and coral has been proposed (Thompson et al, 2015), as it was demonstrated for Endozoicomonas symbionts in corals with contrasting life-history traits and across global scales (Bayer et al, 2013;Neave et al, 2016Neave et al, , 2017.…”
Section: Exaiptasia H2 and Cc7 Strains Only Share A Small Common Micrmentioning
confidence: 99%